Предмет: Алгебра, автор: negreckyi3

упр.711 первый столбик СРОЧНО ПОМАГИТЕ

Приложения:

Ответы

Автор ответа: julyap
0
1)  x^{3} + x^{2} +x+1= x^{2} (x+1)+1(x+1)=\=( x^{2} +1)(x+1) \  \ 2)y ^{5} -y ^{3} -y ^{2} +1=y ^{3} (y ^{2} -1)-1(y ^{2} -1)=\=(y ^{3} -1)(y ^{2} -1)=(y ^{3} -1)(y-1)(y+1) \  \ 3) a ^{4} +2a ^{3} -a-2=a ^{3} (a+2)-1(a+2)= \ =(a ^{3} -1)(a+2) \  \ 4) b ^{6} -3b ^{4} -2b ^{2} +6=b ^{4} (b ^{2} -3)-2(b ^{2} -3)=\=(b ^{4} -2)(b ^{2} -3)
Похожие вопросы
Предмет: Физика, автор: Dka01112001